The transmission characteristics and influence prediction of impulsive vibration caused by a solid metal ball impact in buildings. Issue 2 (June 2023) - Guo, Jingyi; Lin, Qili; Di, Guoqing
The impulsive vibration induced by human running and jumping, object falling, striking during decoration, etc., significantly disturbs the learning, work, and life of people through building structure transmission. To study the influence of impulsive vibration in buildings, a vacant frame building was selected as a tested building. The vibration at each floor besides hitting spot would be measured when a solid metal ball falling freely hit the first floor of this building. The vibration response at each floor caused by the excitation above was simulated through a finite element method. The parameters of the simulation model were optimized according to measured results. Furthermore, the influence of building structure, the total amount of stories, and slab dimension on the transmission of vibration from 1 Hz to 80 Hz which can be perceived by human bodies was quantitatively studied. Results showed that the vertical weighted vibration acceleration level at each floor linearly decreased with the increase of the logarithm of the distance between each floor and the hitting spot. A prediction model of vertical weighted vibration acceleration level from 1 Hz to 80 Hz induced by the impulsive vibration in buildings was developed according to simulation results. The corrections relating to the number of story, building structure, slab span, slab length-to-width ratio, and slab thickness were respectively introduced in the model which can predict the vertical weighted vibration acceleration level at each floor above the hitting spot. The results of this study can provide a basis for the prediction and control of impulsive vibration caused by an impact source with great stiffness in buildings.